2018
DOI: 10.1016/j.stem.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

SETD7 Drives Cardiac Lineage Commitment through Stage-Specific Transcriptional Activation

Abstract: Cardiac development requires coordinated and large-scale rearrangements of the epigenome. The roles and precise mechanisms through which specific epigenetic modifying enzymes control cardiac lineage specification, however, remain unclear. Here we show that the H3K4 methyltransferase SETD7 controls cardiac differentiation by reading H3K36 marks independently of its enzymatic activity. Through chromatin immunoprecipitation sequencing (ChIP-seq), we found that SETD7 targets distinct sets of genes to drive their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 53 publications
2
50
0
Order By: Relevance
“…We generated multiple patient-specific iPSC lines using non-integrating reprogramming methods 7,8 and derived iPSC-CMs using a chemically-defined protocol [8][9][10] to examine the electrophysiological properties at the single cell level. We found that the LMNA-mutant iPSC-CMs (III-3, III-9, III-15, and III-17) exhibited arrhythmias resembling delayed afterdepolarizations (DADs) in both atrial-and ventricular-like iPSC-CMs when compared to healthy controls (IV-1 and IV-2) ( Fig.…”
Section: Modeling Lmna-dcm With Ipsc-cms In Vitromentioning
confidence: 99%
“…We generated multiple patient-specific iPSC lines using non-integrating reprogramming methods 7,8 and derived iPSC-CMs using a chemically-defined protocol [8][9][10] to examine the electrophysiological properties at the single cell level. We found that the LMNA-mutant iPSC-CMs (III-3, III-9, III-15, and III-17) exhibited arrhythmias resembling delayed afterdepolarizations (DADs) in both atrial-and ventricular-like iPSC-CMs when compared to healthy controls (IV-1 and IV-2) ( Fig.…”
Section: Modeling Lmna-dcm With Ipsc-cms In Vitromentioning
confidence: 99%
“…In other cases, SETD7-mediated methylation facilitates recruitment of transcription factors to chromatin (9,10). Finally, methylation of proteins by SETD7 affects protein-protein interaction both in the nucleus and cytoplasm (7,11,12). SETD7 is absent in pluripotent ESCs (11).…”
mentioning
confidence: 99%
“…Finally, methylation of proteins by SETD7 affects protein-protein interaction both in the nucleus and cytoplasm (7,11,12). SETD7 is absent in pluripotent ESCs (11). Its expression is activated once cells transit from pluripotent to multipotent state and further maintained in post-mitotic differentiated cells (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The epigenetic enzyme regulation of the chromatin patterns in cardiac differentiation has been intensely investigated. New study in Cell Stem Cell highlights the role of lysine methyltransferase SETD7 in CM transcriptional programs (2). The authors' observations on striking upregulation of SETD7 upon differentiation of human embryonic stem cell (hESC) to mesodermal progenitors (MES), CM progenitors (CP) and CMs has prompted in depth investigation of the function of this enzyme.…”
mentioning
confidence: 99%